2-C-Methyl-D-allono-1,4-lactone - Harding, C; Watkin, D; Sawyer, N; Jenkinson, S; Fleet, G (2005)
The relative stereochemistry of the compound 2-c-methyl-D-allono-1,4-lactone was established using X ray crystallographic analysis. The absolute stereochemistry was defined by the use of D-ribonolactone as a starting material. All H atoms were observed in a difference electron density map and were refined using slack restraints to optimize their geometry. The crystal structure was made up of layers of strongly hydrogen-bonded molecules, which were found to be lying in the ab plane.